USP1–TRAF2 axis–regulated mortalin stability mediates chemoresistance by disrupting calcium transport in peripheral T-cell lymphoma - Ailing Gui; Yichen Yan; Shiyu Jiang; Feng Chen; Xiaolong Zhou; Qi Sun; Shi Qiu; Jichuan Wu; Xiya Li; Junyi Zhang; Jie Liu; Shun Zhu; et al. (Proceedings of the National Academy of Sciences, 2025)
Ubiquitin-specific peptidase 1 (USP1) plays a critical role in the progression and chemoresistance of various cancers, making USP1 inhibitors a promising therapeutic option in cancer treatment. However, the role of USP1 in peripheral T-cell lymphoma (PTCL) has remained unexplored. Our study uncovers a USP1-dependent survival axis driving chemoresistance in PTCL. USP1 is significantly upregulated in PTCL patients and correlates with poor prognosis through promoting mortalin degradation via TRAF2 deubiquitination. USP1 overexpression enhances TRAF2 stability by reducing its ubiquitination, thereby elevating TRAF2 levels. This, in turn, facilitates mortalin degradation, leading to diminished mortalin expression, reduced mitochondrial localization of mortalin, and impaired apoptosis. Notably, silencing mortalin in PTCL cells further decreases sensitivity to doxorubicin and suppresses apoptotic pathways. Mechanistically, reduced mitochondrial localization of mortalin disrupts calcium transport between the endoplasmic reticulum and mitochondria through the IP 3 R–mortalin–VDAC1 complex. The impaired calcium shuttling triggers the activation of NF-κB and JAK-STAT signaling pathways, ultimately attenuating apoptosis. Importantly, pharmacological inhibition of USP1 with ML323 effectively enhances PTCL cell sensitivity to doxorubicin, suggesting a promising therapeutic strategy to improve treatment outcomes in PTCL patients. Collectively, we have found that USP1 represents a compelling therapeutic target for addressing chemoresistance and improving outcomes in PTCL therapy.